2022
DOI: 10.1371/journal.pone.0261216
|View full text |Cite
|
Sign up to set email alerts
|

What are the risk factors of hospital length of stay in the novel coronavirus pneumonia (COVID-19) patients? A survival analysis in southwest China

Abstract: Background The global epidemic of novel coronavirus pneumonia (COVID-19) has resulted in substantial healthcare resource consumption. Since patients’ hospital length of stay (LoS) is at stake in the process, an investigation of COVID-19 patients’ LoS and its risk factors becomes urgent for a better understanding of regional capabilities to cope with COVID-19 outbreaks. Methods First, we obtained retrospective data of confirmed COVID-19 patients in Sichuan province via National Notifiable Diseases Reporting S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
(21 reference statements)
2
18
0
3
Order By: Relevance
“…Mahboub et al found that diagnosis at admission, painkiller usage, ventilator intubation, azithromycin usage, antiviral usage, anti-inflammatory agent usage, vitamin C usage, urea test results, platelet count, haemoglobin levels, dimer levels, and potassium levels were significant predictors of LoHS [ 39 ]. Moreover, Wang et al reported that age and clinical grade were strongly related to the length of stay ( p < 0.01) and that a longer LoHS was associated with ≥45 years of age, severe illness, and admission to a provincial hospital [ 40 ]. Our results of prolonged LoHS among patients with either severe or critical symptoms were aligned with Wang et al’s findings.…”
Section: Discussionmentioning
confidence: 99%
“…Mahboub et al found that diagnosis at admission, painkiller usage, ventilator intubation, azithromycin usage, antiviral usage, anti-inflammatory agent usage, vitamin C usage, urea test results, platelet count, haemoglobin levels, dimer levels, and potassium levels were significant predictors of LoHS [ 39 ]. Moreover, Wang et al reported that age and clinical grade were strongly related to the length of stay ( p < 0.01) and that a longer LoHS was associated with ≥45 years of age, severe illness, and admission to a provincial hospital [ 40 ]. Our results of prolonged LoHS among patients with either severe or critical symptoms were aligned with Wang et al’s findings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported mean LOSs of patients with COVID-19 of 5–17 days [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]; the differences in the reported values can be attributed to the times at which the studies were conducted (e.g., early 2020 vs. late 2021); severity, treatment guidelines, admission, and discharge criteria; regional prevalence of COVID-19; and even regional rates of COVID-19-related mortality [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. More comprehensive information regarding the prediction of the LOSs of patients with COVID-19 can improve the efficiency of medical resource allocation and ameliorate prognosis [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous studies that have tried to find the predictors of the length of hospitalization in COVID-19 patients [ 15 , 16 , 17 ]. However, a patient’s mobility status and muscle strength are rarely considered.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, identifying risk factors of a prolonged hospitalization in patients with COVID-19 is also a crucial issue. There are numerous studies that have investigated the risk factors regarding a prolonged hospitalization period [ 15 , 16 , 17 ]. Wu et al [ 17 ] and Liu et al [ 15 ] discovered that high fever, bilateral pneumonia seen on a chest computed tomography, diabetes, and lymphopenia can all predict longer hospitalization.…”
Section: Introductionmentioning
confidence: 99%